2004
DOI: 10.1007/s00104-003-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

Die homologe Venentransplantation zur kruropedalen arteriellen Rekonstruktion

Abstract: Allogenic venous transplantation represents an alternative procedure for preventing leg amputation. This study reviewed the question of whether immunologic monitoring and immunosuppressive therapy provide results close to those of autologous reconstructions. Twenty-eight patients received 31 homologous venous transplants. The average age in this group of 15 women and 13 men was 64.5 years. Limbs in danger of amputation could be kept longer in two thirds of them. These promising results show the superiority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…The immunosuppressive therapy after alloarterial or allovenous reconstructions is not generally accepted. However, if the therapy is administered, the drug most frequently used (mainly in Europe) is cyclosporine A (CyA) [8–13]. However, it has been demonstrated that CyA can induce endothelial cell (EC) injury, as well as stimulate arterial wall fibrosis by triggering the production of the transforming growth factor‐beta (TGF‐beta) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The immunosuppressive therapy after alloarterial or allovenous reconstructions is not generally accepted. However, if the therapy is administered, the drug most frequently used (mainly in Europe) is cyclosporine A (CyA) [8–13]. However, it has been demonstrated that CyA can induce endothelial cell (EC) injury, as well as stimulate arterial wall fibrosis by triggering the production of the transforming growth factor‐beta (TGF‐beta) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Dlouhý bypass k arteria dorsalis pedis nebo arteria tibialis posterior je možností, jak zachránit ischemickou končetinu, jestliže chybí cílová tepna uložená proximálněji. Alogenní transplantace štěpu z vena saphena představuje u kritické ischemie končetiny ultimum refugium v případě pacientů s rozsáhlým a končetinu ohrožujícím postižením tepen, u nichž byly autologní náhrady vyčerpány nebo nejsou k dispozici v dostatečné kvalitě a délce [1,2]. Tuto techniku zavedl do praxe roku 1948 Jean Kunlin.…”
Section: úVodunclassified
“…In der operativen Therapie der kruralen und pedalen arteriellen Verschlusskrankheit besteht eine Stagnation: Die autologe V. saphena magna gilt aufgrund exzellenter Offenheitsraten von 68 bis 85 % gegenüber 30 bis 59 % bei Verwendung von alloplastischem Prothesen als Gefäßersatz der ersten Wahl [1][2][3][4][5][6][7]. Trotz guter Ergebnisse auch bei Transplantation der V. saphena magna mit Immunsuppression [8,9] bleibt die Verfügbarkeit derselben limitiert. Alloplastische Gefäßprothesen werden seit 50 Jahren erfolgreich in der Rekonstruktion arterieller Verschlussprozesse Zusammenfassung !…”
unclassified